2005
DOI: 10.1111/j.1365-2702.2005.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Speculum ‘self‐insertion’: a pilot study

Abstract: Speculum self-insertion may encourage women's attendance at clinics for regular screening. Early diagnosis and treatment will result in better health outcomes for women, families and the community at large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Alternative positions,10 alternative speculums,11 alternative foot rests,12 self insertion of the speculum,13 and different types of gowns14 have shown varying degrees of improvement in pain, embarrassment, or anxiety. Reduction of physical discomfort and psychological distress are part of the motivation for the recent attempts to validate self collection methods for cervical cancer screening to eliminate the need for smears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative positions,10 alternative speculums,11 alternative foot rests,12 self insertion of the speculum,13 and different types of gowns14 have shown varying degrees of improvement in pain, embarrassment, or anxiety. Reduction of physical discomfort and psychological distress are part of the motivation for the recent attempts to validate self collection methods for cervical cancer screening to eliminate the need for smears.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of physical discomfort and psychological distress are part of the motivation for the recent attempts to validate self collection methods for cervical cancer screening to eliminate the need for smears. 15 16 Some studies have shown that beliefs about pain during the procedure can influence screening behaviours for some women 13…”
Section: Discussionmentioning
confidence: 99%
“…A study of 354 women in Moshi, Tanzania revealed that key factors for cervical cancer screening were significant concerns about embarrassment and pain due to screening from the speculum as well as physician gender [7]. In Australia, a study seeking to determine women’s attitudes towards physician versus self–insertion of the standard speculum found that 91% of 133 women would choose self-insertion over physician insertion, and that women have indicated discomfort, embarrassment and vulnerability from having another person insert a device and examine their cervix [8]. In the U.S., even though there is greater access to health care, compliance rates to cervical cancer screening vary, and embarrassment and fear of pain during examination have been reported as potential barriers to screening [7, 911].…”
Section: Introductionmentioning
confidence: 99%
“…An Australian study of women attending family planning clinics found that 67% (133/198) agreed to insert their own speculum, and of these, 90% would choose to do it again. The main barrier was women feeling unsure how to self insert a speculum 6. In future, screening might be based on detection of specific human papillomavirus (HPV) subtypes and additional biomarkers for risk of cervical cancer.…”
mentioning
confidence: 99%